Dose assessment for patients with stage I non-small cell lung cancer receiving passive scattering carbon-ion radiotherapy using daily computed tomographic images: A prospective study. (March 2020) - Li, Yang; Kubota, Yoshiki; Kubo, Nobuteru; Mizukami, Tatsuji; Sakai, Makoto; Kawamura, Hidemasa; Irie, Daisuke; Okano, Naoko; Tsuda, Kazuhisa; Matsumura, Akihiko; Saitoh, Jun-ichi; Nakano, Takashi; et al.
Highlights: All patients' accumulated doses were satisfactory using tumor matching. Bone matching may lead to hypofractionated carbon ion therapy failure. Tumor matching enables a smaller required margin. Daily CT alignment is necessary for patients with non-small cell lung cancer. Abstract: Background and purpose: This study aimed to assess dose distributions for stage I non-small cell lung cancer (NSCLC) with passive scattering carbon-ion radiotherapy (C-ion RT) using daily computed tomography (CT) images. Materials and methods: We enrolled 10 patients with stage I NSCLC and acquired a total of 40 pre-fractional CT image series under the same settings as the planning CT images. These CT images were registered with planning CT images for dose evaluation using both bone matching (BM) and tumor matching (TM). Using deformable image registration, we generated accumulated doses. Moreover, the volumetric dose parameters were compared in terms of tumor coverage and lung exposure and statistical analyses were performed. Results: Overall, 25% of 40 fractional dose distributions were unacceptable with BM, compared with 2.5% with TM ( P  < 0.001). Using BM, three patients' accumulated dose distributions were unacceptable; however, all were satisfactory with TM ( P  < 0.001). No differences were observed in water-equivalent path length (WEL). The required margins in patients with poor dose distribution were 5.9 and 4.4 mm for BM and TM, respectively. Conclusions: This study establishes that CT image-based TM is robust compared with conventional BM for both daily and accumulated dose distributions. The effects of changes in WEL seem to be limited. Hence, daily CT alignment is recommended for patients with stage I NSCLC receiving C-ion RT.